Wet granulation method in the technology of 6,8-dimethyl-2-piperidinomethyl-2,3-dihydrothiazolo[2,3-F]xanthine tablets, which increases the detoxifying function of the liver - A. I. Petrakov; V. V. Sheikin; S. V. Krivoshchekov; A. M. Guryev; M. V. Belousov (Разработка и регистрация лекарственных средств, 2025)
Introduction. 6,8-dimethyl-2-piperidinomethyl-2,3-dihydrothiazolo[2,3-F]xanthine is a promising substance-inducer of the monooxygenase system of hepatocytes, according to preclinical studies, increasing the detoxifying function of hepatocytes in models of acute hypobaric hypoxia, liver ischemia, unconjugated hyperbilirubinemia, toxic hepatitis. Previously, the possibility of tablets based on 6,8-dimethyl-2-piperidinomethyl-2,3-dihydrothiazolo[2,3-F]xanthine by direct pressing was shown. However, during the development process, with an increase in batch volumes of tablet masses, insufficient completeness of loading of the tablet press matrix was revealed. This is due to the low flowability of the tablet mass. This led to a deterioration in the uniformity of dosage and the appearance of defects in the average weight. During pharmaceutical development was made to use the wet granulation method to obtain 6,8-dimethyl-2-piperidinomethyl-2,3-dihydrothiazolo[2,3-F]xanthine tablets to improve the technological properties of the tablet mass. The composition of filler excipients (lactose monohydrate and microcrystalline cellulose), tablet form, and parameters of quality preserved. For this aim the influence of binders, antifriction agents and granule size on the technological properties of the tablet mass was studied. The crushing strength and disintegration of the tablets analyzed.Aim. Development of a composition for wet granulation of 6,8-dimethyl-2-piperidinomethyl-2,3-dihydrothiazolo[2,3-F]xanthine to obtain granules with optimal technological parameters to obtain high-quality tablets that pass tests according to the State Pharmacopoeia of the Russian Federation.Materials and methods. To obtain granules, 6,8-dimethyl-2-piperidinomethyl-2,3-dihydrothiazolo[2,3-F]xanthine of the DPDTX280424001 series was used as a starting material. Lactose monohydrate (200-559-2, LLC "Neftegazkhimkomplekt", Russia), microcrystalline cellulose (100-32-2, Silverline chemicals Ltd., India), potato starch and hydroxypropylcellulose (ZW180113, Fengchen Group Co., Ltd., China) were used as filler excipients. 5 % polyvinylpyrrolidone gel, 5 % starch mucus and 5 % hydroxypropyl methylcellulose gel were considered as binder excipients. Magnesium stearate (209-150-3, Ataman Chemicals, Türkiye), calcium stearate and talc (LLC "Agat-Med", Russia) were used as antifriction agents. Tablet masses assessed in terms of the force of ejection of the tablet from the matrix, flowability, bulk density, and compressibility. An EP-1 tablet press (ERWEKA GmbH, Germany) used as a press machine. The crushing strength, disintegration, and average weight of the resulting tablets assessed. Tests carried out in accordance with the State Pharmacopoeia of the Russian Federation.Results and discussion. Based on the Latin square using the Harrington desirability function with analysis of variance of experimental data, it was found the greatest effect on the flowability of granules is on the granule size (influence to 77.68 %, granule size 0.5–1 mm). Influence of binder excipients to disintegration and crushing strength reached to 99.38 and 95.35 %. 5 % starch mucus as a binder excipient for obtain to granules possible to improve the flowability of the tablet mass from 3.5–4.0 to 12.5–12.9 g/s in comparison with the direct pressing method. The crushing strength and disintegration tests were successfully completed.Conclusion. As a result of the experiments, the effect of wet granulation on the technological properties of the tablet mass of 6,8-dimethyl-2-piperidinomethyl-2,3-dihydrothiazole[2,3]-F-xanthine was studied. The obtained granules had improved flowability compared to the initial tablet mass. This made it possible to ensure a more complete filling of the tablet press matrix, better uniformity of dosage, eliminate tablet defects and maintain strength and disintegration compared to direct pressing. The improvement of flowability due to granulation also makes it possible to consider capsules and sachets as alternative dosage forms for 6,8-dimethyl-2-piperidinomethyl-2,3-dihydrothiazolo[2,3-F]xanthine.